OiSeminar Edukasi Narkoba sebagai Upaya Membentuk Generasi Sehat Tanpa Narkoba - Bintang R N Hutagalung; Syofiah Sinaga; Putri Ramadani; Juita Khairunnisa; Nur Aisyah Pandia; Miko Ananda Daulay; Laila Rohani (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
For young individuals who are readily swayed by their surroundings and social networks, drug misuse is a severe issue. The purpose of this study is to outline the drug seminar that was implemented at SMP Negeri 01 Laut Tador as a preventative strategy to produce a generation that is drug-free and healthy. The seminar, held on August 9, 2025, was attended by all students, with speakers from the 2025 UINSU Community Service Program (KKN) students. The methods used in this activity included material delivery, interactive discussions, and a question and answer session. According to the study's findings, the seminar was a success, the students were eager to participate, and they demonstrated a greater comprehension of the many kinds of drugs, their effects on health, social, and legal elements, as well as prevention strategies.The interactive discussion also increased students' active participation in expressing opinions and asking questions. These findings indicate that drug seminars are effective in increasing students' knowledge, awareness, and commitment to staying away from illegal drugs. Therefore, activities like this can be an important preventive approach in efforts to build a healthy, intelligent, and drug-free young generation.